Measurements of 12 C ion fragmentation on thin carbon target from the FIRST collaboration at GSI. (March 2015) - Toppi, M
Abstract: The FIRST (Fragmentation of Ions Relevant for Space and Therapy) experiment at GSI laboratory took data in summer 2011, studying the collisions of a 12 C ion beam with Carbon and Au thin targets. The experiment main purpose is the double differential cross section measurement of the carbon ion fragmentation at energies that are relevant both for tumor therapy and space radiation protection applications (100-1000 MeV/u). The FIRST dataset contains carbon ions collisions on a 3.43 g·Cin −2 carbon target (about 24 M events) and on a 0.96 g·cm −2 Au target (about 4.5 M events). The SIS (heavy ion synchrotron) was used to accelerate the 12 C ions at the energy of 400 MeV/u. The preliminary results of differential cross sections measurements as a function of angle and energy for carbon target, in the small angle region (θ ≤ 5°), are presented.